Comparing skill enhanced and standard cognitive behavioral therapy for depression: a protocol for a randomized trial - Murphy, Samuel T.; Bailey, Brooklynn; Bartels, Graham C.; Vittorio, Lisa N.; Whelen, Megan L.; Zhou, Robert J.; Strunk, Daniel R. (International Journal of Clinical Trials, 2021)
Background: Cognitive behavioral therapy (CBT) features prominently among the first-line treatments for depression. The development of CBT skills is associated with both symptom reductions and reduced risk for relapse, suggesting that improvements in CBT skills might be important to the benefits of CBT. Nonetheless, standard CBT places modest emphasis on the development of these skills. Methods: In this paper, we describe a randomized clinical trial testing the benefits of a variation of CBT that places greater emphasis on teaching patients CBT skills and makes patients' independent use of these skills a central therapeutic goal. Patients in this study (75 per condition) are being randomized to 12 weeks of standard or skill enhanced CBT for depression. The primary outcomes are change in symptoms and change in CBT skills. We will also evaluate the process of change in the treatments. Conclusions: This study has the potential to suggest an approach to enhancing CBT outcomes through greater focus on patients developing and independently using CBT skills. It will also provide an important context for understanding the role that CBT skills play in the therapeutic outcomes of CBT. Trial registration: The trial has been registered in ClinicalTrials.gov. Registration number: NCT04673513; registered on 17 December 2020.